Kinematics and orientation capability of a family of 3-DOF parallel mechanisms. (December 2019) - Peng, Binbin; Zhu, Shuai; Khajepour, Amir; Huang, Yanjun
Highlights: The general framework of 35 combination mechanisms with the same topology. Establishing the unified kinematic model of these 35 mechanisms. The coupling relationship between the six output parameters of these 35 mechanisms. Proof of kinematics for linear Delta mechanism from the perspective of geometry. The influence of scale parameters on the orientation capability. Abstract: Existing research demonstrates that the linear Delta robot and the 3-PRS parallel manipulator are different from each other. In this paper, by changing the dimensional parameters of the 4S mechanism in the limb of linear Delta, 35 combinations with the same topology are obtained. The linear Delta and the equivalent 3-PRS parallel manipulator are included in these mechanisms. The unified kinematic model of these 35 mechanisms is established and their possible kinematic characteristics are analyzed as well. According to the constraint requirements of input, the coupling relationship just between the six output parameters of these 35 mechanisms is derived. In addition, the sufficient and necessary conditions for the Delta mechanism to achieve translational motion are demonstrated from the perspective of geometry. By changing dimensional parameters of the 4S mechanism in the chain, its influence on the orientation capability is studied. The coupling relationship just between the six output parameters of the 3-PRS or 3-PSR parallel mechanisms can be easily revealed by the unified kinematic model and the constraint equations. The relationship between the orientation capability and the dimensional parameters indicates that the dimensional parameters can affect the output kinematic characteristics which is not a singularity.